Long‐term follow up of renal anastomosing hemangioma mimicking renal angiosarcoma. (20th March 2014) - Heidegger, Isabel; Pichler, Renate; Schäfer, Georg; Zelger, Bernhard; Zelger, Bettina; Aigner, Friedrich; Bektic, Jasmin; Horninger, Wolfgang
Abstract Anastomosing hemangioma of the kidney is a very rare neoplasm, currently 19 cases have been reported in the literature. First described in 2009, histopathologically anastomosing hemangioma is similar to aggressive angiosarcoma. No long‐term follow‐up data of anastomosing hemangioma have been described yet. Here, we present the case of a healthy 56‐year‐old man diagnosed in 2002 with a 7 × 5‐cm anastomosing hemangioma mimicking an aggressive renal angiosarcoma. The patient underwent nephrectomy and has been followed up disease free for 13 years.